The Benefits of Dates Ruthab on Blood Volume On Labor Stage 4th - Purnama, Agus; Melawati, Mua (Journal Of Nursing Practice, 2019)
Background: Birth is a natural process and is a physiological condition in a woman. there are 4 stage/times in labor which are 1st time, 2nd time, 3rd time and 4th time. The effort used to facilitate labor is to make contractions and relaxation effective. dates contain tannins which can shorten bleeding time and high glucose as a good source of energy during labor. Purpose: The purpose of this study is to see at the amount of bleeding in the group not given dates and given date ruthab. Method: this study using a quasi-experimental method in two different groups with 34 people treated with primigravida with 17 control groups and 17 intervention groups. given treatment for 4 weeks before the estimated delivery and check the blood volume with a measuring cup.Result: The results showed a significance value of the results of the t-test, namely: 0,000 for the 4th stage, the value was smaller than the significance level (?) of 0.05, meaning Ho was rejected, so it could be decided the hypothesis of the effect of giving wet dates to decreasing blood volume in stage 4th labor can be accepted.Conclusion: dates ruthab can be used as supporting therapy in the labor process and has very convincing benefits